Canine pancreatic islet cell tumours secreting insulin‐like growth factor type 2: a rare entity. (16th January 2014) - Finotello, R.; Ressel, L.; Arvigo, M.; Baroni, G.; Marchetti, V.; Romanelli, G.; Burrow, R.; Mignacca, D.; Blackwood, L.
Abstract: Insulin‐like growth factor type II (IGF‐II) is the main cause of non‐islet cell tumour hypoglycaemia (NICTH) and insulin is thought to be the only factor causing hypoglycaemia in insulinomas. However, two case reports of pancreatic neuroendocrine tumours (PNETs) producing IGF‐II have been previously published: a human and a canine patient. In this study, we investigated clinical, histopathological, immunohistochemical and ultrastructural features, and biological behaviour of canine pancreatic IGF‐II‐omas, a subgroup of PNETs that has not been previously characterized. Case records of 58 dogs with confirmed PNETs and hypoglycaemia were reviewed: six patients were affected by IGF‐II‐omas. Surgery was performed in all cases and two dogs had metastases. Four patients remained alive and in remission at 370, 440, 560 and 890 days post‐diagnosis; two died of non‐tumour‐related causes. IGF‐II‐omas can be differentiated from insulinomas through hypoinsulinaemia, IGF‐II positive and insulin negative immunostaining. The prevalence of this neoplasia is low, accounting for just 6% of PNETs.